JUSTIFICATION OF FILLERS USING IN THE BEARING STRUCTURES COMPONENTS OF FREIGHT CARS (Transport systems and technologies, 2021)
To reduce the load on the freight cars frames under operational conditions, it has been suggested that to use fillers in their components. Fillers using is advisable in the most loaded elements of the bearing structure, namely, the spine beam. Therefore, a necessary condition for filler using in the spine beam is the creation of its closed structure. The dynamic load of railcars was carried out, taking into account the proposed provisions. Calculations have shown with filler using, the maximum accelerations acting on the bearing structures of wagons are 4% lower than those accelerations obtained for bearing structures without fillers.The results of determining the main strength indicators of bearing structures of freight cars are presented, taking into account the fillers using in their components. It has been established that the strength of the frames of the considered types of wagons under the main operating conditions is ensured. At the same time, the maximum equivalent stresses in the bearing structures of wagons are 4-9% lower than those in typical frame structures.The conducted research will contribute to the creation of innovative structures of rolling stock and reduce the cost of its maintenance work in operation.
Keywords: wagon, bearing structure, spine beam, dynamic loading, strength.